Facebook for intercultural communication: The foreign students experience - Raja Zainal Hassan, Raja Rodziah; Hassan, Nor Azlili; Sallehuddin, Iza Sharina; Abdul Aziz, Nik Norazira (Universiti Utara Malaysia Press, 2020)
Computer-mediated communication has been an integral part of how people communicate in todays modern society. The study of the impact of social media on intercultural competency is still in its infancy and has intrigued many scholars and researchers. An integral part of a foreign university students experience in a host country is to manage cultural differences. Hence, through the use of computer-mediated communication by foreign university students, a better understanding of the impacts of social media (Facebook) on intercultural learning experiences can be achieved. The aims of this study are: 1) to analyse the experience of foreign university students that uses Facebook to communicate with their local peers 2) to examine Facebook usage pattern(s) among foreign university students in Malaysia, and 3) to determine the level of intercultural competency among foreign university students in Malaysia. This study employs the Intercultural Sensitivity Scale (ISS), developed by Chen and Starosta (2000), to analyse the communication patterns of foreign university students in Malaysia that uses Facebook as a platform to learn and cope with cultural differences. This study analysed data from the survey of 210 foreign university students in Klang Valley, Malaysia. The findings from this study suggest that the majority of foreign university students enjoy communicating with their local peers from different cultures by using Facebook. Moreover, the findings indicate that foreign university students are confident when communicating with their local friends, and further concludes that the foreign students are culturally competent. These findings were determined by examining online interactions between foreign students and their local peers, and through Facebook usage patterns obtained from their experience.